Dynamic fracture initiation toughness of PMMA: A critical evaluation. (March 2016) - Faye, Anshul; Parameswaran, Venkitanarayanan; Basu, Sumit
Highlights: Using max. load as indication of dynamic fracture initiation overestimates the toughness. Crack initiation detected by surface gauges overestimates the fracture initiation time. Initial defect spreads radially at close to the Rayleigh wave speed in the material. Dynamic fracture initiation toughness of PMMA falls slightly below the static value. Abstract: Fracture toughness of the brittle amorphous polymer polymethyl methacrylate (PMMA) has been reported to decrease with loading rate at moderate rates and increase abruptly thereafter to close to 5 times the static value at very high loading rates. Dynamic fracture toughness that is much higher than the static value has attractive technological possibilities. However, the reasons for the sharp increase remain unclear. Recent work on another amorphous polymer, Polycarbonate (PC), has shown that the existence of this phenomenon depends sensitively on the definition of the term "fracture initiation". Difficulties associated with the visualisation of the very early stages of defect nucleation constrain us to use indirect pointers to determine fracture initiation. Following on the work of Faye et al. (2015) on PC, we have (i) used ultra high speed imaging to time very early stages of defect nucleation ahead of a notch, and, (ii) concurrently conducted Finite Element simulations using a well-calibrated viscoelastic model for PMMA, in order to gain insights into the phenomenon of amplification of fracture initiation toughness at high loading rates. Our results suggest that toughness at the initiation of early defects in PMMA is somewhat lower at high loading rates. It seems that toughness amplification results from use of either surface gauges or the attainment of maximum load as indication of crack initiation. The fact that the crack front in PMMA may not be perfectly straight leads to a lower value of initiation toughness.